Exploring The Impact of Job Insecurity and Social Support on Hotel Employees in Bandung's Tourism Sector - Retnowati, Ayu Nike; Puspita, Mugi; Julianti, N Sahla; Sitorus, Veronica Rohali (Indonesian Scientific Publication, 2025)
This research aims to determine the responses of sandwich generation employees who work in the tourism industry hospitality sub-sector in the city of Bandung and assess the influence of Job insecurity and social support on Burnout partially or simultaneously. The method used in this research is descriptive and verification with a quantitative approach. The population used in this research is generational employees sandwich in the Bandung City hospitality sub-sector tourism industry, with a sample of 160 respondents using non-probability sampling techniques, namely accidental sampling. Based on the research results, it was found that the respondents' responses were related to job insecurity, which was included in the high category, namely social support, which was included in the low category; and burnout, which was included in the high category. Based on the results of the determination test, it was found that Job insecurity has an effect of 12.9% on Burnout, Social support has an effect of 9.3% on Burnout, and Job insecurity and Social support have an impact of 12.3% on Burnout. Based on the results of partial hypothesis testing, Job insecurity affects Burnout. Social support does not affect Burnout. Based on the results of hypothesis testing, Job insecurity and Social support simultaneously influence Burnout.